Water-Yield Relationships of Potato in Mediterranean Climatic Conditions - Yasemin Beyza Şahin; Yusuf Uçar; Arif Şanlı (Turkish Journal of Agriculture: Food Science and Technology, 2023)
This study was carried out in Isparta University of Applied Sciences, Faculty of Agriculture, Agricultural Research, and Application Farm in 2021 to determine the effect of different irrigation water levels on tuber yield and quality parameters of the Agria potato variety. Drip irrigation method was used in the study and five different irrigation water levels (S1: 120% of the seven-day ETo, S2: 90% of the seven-day ETo, S3: 60% of the seven-day ETo, S4: 30% of the seven-day ETo, S5: No irrigation except germination and emergence) were determined based on the reference evapotranspiration (ETo). Irrigation water (IW) amounts varied between 85.66-639.26 mm and evapotranspiration varied between 296.54-825.15 mm. Different amounts of IW significantly affected the vegetative growth, yield and quality parameters of potato. As irrigation water decreased, total tuber yield and marketable yield declined. Total tuber yield and marketable yield were 46.11 t/ha and 40.59 t/ha, respectively, in S1 treatment where the maximum amount of IW was applied, while they were 12.96 t/ha and 6.37 t/ha, respectively, in S5 treatment where no irrigation was applied. Logarithmic relationships were determined between evapotranspiration and total yield and between the amount of IW and total yield. Water use efficiency was determined between 43.69-55.88 kg/(ha×mm) and irrigation water use efficiency between 32.34-51.86 kg/(ha×mm) and yield response factor (ky) was calculated as 1.19.